Increasing the Efficiency of the European Institutions: A Historical Perspective - Ionut Popescu (CES Working Papers, 2010)
The view that European institutions do not operate with maximum efficiency, that they are not yet able to cope with all major economic and social problems, to fully meet the basic functions, thatcannot adapt to rapidly changing world has not emerged in recent years. In this paper we try to clarify the concept of institutional efficiency, and try to follow from a chronological perspective the main events that led to the more or less efficient European institutions.
Keywords: 330; Institutions; efficiency; European Union